Artificial intelligence in education: advancing educational digital inclusion for adults older with diverse neuromuscular conditions - Paula Andrea Valencia-Londoño; Hilderman Cardona-Rodas; Jovani A. Jiménez-Builes (Frontiers in Education)
This research evaluates the potential of Artificial Intelligence (AI) interventions in promoting digital inclusion for older adults with neuromuscular conditions, aligning with Sustainable Development Goal (SDG) 4 for equitable education. Using a mixed-methods approach, we combined quantitative measures of digital literacy and engagement with qualitative insights into user experiences. The findings reveal statistically significant advancements in digital literacy (p < 0.001) and engagement metrics (p < 0.01), highlighting the transformative potential of adaptive learning platforms, virtual reality applications, and interactive mobile tools tailored for this population. Participants reported increased confidence and empowerment, emphasizing the importance of user-centered design and accessibility in technology development. While the study demonstrates short-term benefits, it acknowledges limitations, including a small sample size (n = 30) and the absence of longitudinal data. Future research should explore scalable implementations and long-term impacts, particularly for broader demographic groups and other disability types. These insights provide actionable recommendations for educators, developers, and policymakers aiming to reduce the digital divide and foster inclusive education.